JOB SATISFACTION AS A CORRELATE OF BUSINESS EDUCATORS WORK ADJUSTMENT IN COLLEGES OF EDUCATION IN DELTA STATE (NAU Journal of Technology and Vocational Education, 2024)
The need to enhance job satisfaction and minimize the rate of brain drain experienced bybusiness educators in colleges of education necessitated this study. This study examined jobsatisfaction as correlate of business educators work adjustment in colleges of education in DeltaState. The study adopted the correlation research design. The population of for the studycomprised 82 full time business educators in colleges of education in Delta state. Theinstruments for data collection were structured questionnaire. The questionnaire was validatedby three experts with the reliability Coefficients of 0.71 and 0.81 respectively, established usingCronbach alpha’s method. Data collected were analysed using Pearson product momentcorrelation analysis and linear regression analysis. The findings of this study revealed that a highpositive relationship of 0.700 exists between job satisfaction and work adjustment of businesseducators with 1-9 years work experience, while, a moderate positive relationship of 0.571 existsbetween job satisfaction and work adjustment of business educators with 10 years and abovework experience in colleges of education. On the other hand, there was a statistically significantcorrelation between job satisfaction and work adjustment of business educators with 1-9 yearswork experience and no statistically significant relationship for those with 10 years and abovework experience. Based on the findings of this study, it was recommended that motivationalneeds of business educators should be continually addressed for enhanced productivity.
Keywords: Job satisfaction, work adjustment, business education, business educators, colleges of education.